The Implemantation of Islamic Character Through Developing Material of Indonesian Language in 3rd Grade of Islamic Elementary School - Moch. Bahak Udin By Arifin; Kurnia Laili Fitria (Universitas Muhammadiyah Sidoarjo, 2017)
This research has purpose to implementation of Islamic characteristic by developing material intensive reading of Indonesian language for third grade of Islamic elementary school Darussalam Sidoarjo. From the result of this research will produce a teaching material be in the form of intensive reading text book based on Islamic character for third grade of Islamic elementary school. This research used Research and Development (R&D) method or research development by using developing model of Walter Dick and Lou Carey. The instrument that used to collecting data is exercise test, questionnaire and rating scale. By the implementation of Islamic character in the teaching material of Indonesian language, there should to integrated in value of Islamic character, religious and responsible to the material, implicitly, showing through the picture illustration , narration and teaching learning activity that has been done. From the result of assessment and analysis from all of third grade students of Islamic elementary school Darussalam Sidoarjo has shown the improvement and use religious and responsible character.